Pengaruh Faktor-Faktor Fundamental dan Teknikal terhadap Harga Saham Industri Manufaktur - Farhan Said Hidayat; Gendro Wiyono; Ratih Kusumawardhani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the effect of fundamental variables (Ratio On Assets, Debt to Equity Ratio and Current Ratio) and technical factors (Past Stock Price and Trading Volume) partially and simultaneously on stock prices by using panel data analysis. The sample selection in this study used a purposive sampling method, resulting in 8 manufacturing companies registered on LQ45 in 2017-2021 as samples. The results of this study indicate that: 1) Return On Assets, Debt to Equity Ratio, Current Ratio and Sales Volume partially have no effect on stock prices; 2) Past Share Prices partially have a significant positive effect on stock prices; 3) Return On Assets, Debt to Equity Ratio, Current Ratio, Past Stock Prices, and Trading Volume simultaneously have a significant effect on stock prices. The results of the R2 determination coefficient test show that the variability of the dependent variable (stock price) can be explained by the independent variables (Return On Assets, Debt to Equity Ratio, Current Ratio, Past Stock Prices, and Trading Volume) of 88%, so that the remaining 12% the dependent variable is explained by other factors that the researchers did not input into the study. Keywords: Stock Prices, ROA, DER, CR, Past Stock Prices, and Trading Volume